Revolusi Teknologi: Masa Depan Kecerdasan Buatan (AI) dan Dampaknya Terhadap Masyarakat - Afandi, Ahmad Rickianto; Kurnia, Heri (Universitas Cokroaminoto Yogyakarta, 2023)
In recent years the development of the world of technology has accelerated. One of the hotly discussed technological developments is Artificial Intelligence. Artificial intelligence is the ability of machines to imitate and perform tasks that would normally require human intelligence. This article was created to explore the future development of AI and its impact on society. This article uses the library research method, which is a research approach that collects and analyzes information published in the form of scientific literature, including journal articles, books, research reports, and other sources. From a literature study or library research, it can be concluded that the development of AI and its impact on society, namely, the impact on work and the economy, the impact on health and medical services, the impact on ethics and privacy, and the impact on education.